Immunity in Parkinson's disease – The role of innate responses - Iyengar, A.R. Satvik; Dunkley, Peter R.; Dickson, Phillip W. (Journal of neuroimmunology, 2025)
Parkinson's disease (PD) is a debilitating neurodegenerative disorder that is characterized by motor dysfunction and deterioration of quality of life. PD is caused by a selective degeneration of the dopaminergic neurons in the substantia nigra region of the mid brain. Although, centuries have passed since the identification of PD, the exact pathogenic mechanism of PD is yet to be defined. It is understood that PD is a multifactorial disease that involves several cellular processes including immunological dysfunction. This review provides a brief introduction to PD and the innate immune system. It then elaborates on the role of the innate immune system in PD, in the context of neuroinflammation and the cellular components including microglia and astrocytes. It then explores the association between neuroinflammation, complement system, excitotoxicity, oxidative stress, dopamine metabolism, tyrosine hydroxylase and blood brain barrier in relation to PD. Finally, the review deliberates upon and proposes various diagnostic and therapeutic strategies based on the innate immune system that could be utilised to target the immunological mechanisms participating in PD. [Display omitted] •Aberrations in the immune system could contribute towards pathogenesis and progression of PD.•Components of the innate immune system, e.g., microglia and astrocytes, exhibit a neuroinflammatory profile in PD models and post-mortem subjects.•Neuroinflammation appears to be associated with several mechanisms linked with PD.•Treatments that reduce or alleviate the aggravated innate responses could prove to be beneficial in PD.